Analisa Rendahnya Pendataan Penduduk Non Permanen Di Kota Payakumbuh Dengan Menggunakan Metoda Grounded Theory - Haryanti, Usfa; Aulia, Arif; Iswara, Novi; Haikal, Jerry (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
The movement of people from one place to another is getting faster and wider, this is indicated by the large number of residents who are not native to a certain area but live and settle in that area for a long time. These residents are called non-permanent residents. With the increased mobility of non-permanent residents, it is necessary to describe the condition and development of non-permanent residents as well as the availability of data on non-permanent residents in provinces, districts/cities. The Payakumbuh City Population and Civil Registration Office as the implementing agency is responsible for carrying out non-permanent population data collection. This is in accordance with Permendagri Number 14 of 2015, that Implementing Agencies are district/city government apparatus that are responsible and have the authority to carry out services in Population Administration matters. However, the implementation of Non-Permanent Population Data Collection is not easy, and has not been fully running well. This study aims to identify what are the obstacles in collecting data on non-permanent residents. The analysis carried out includes the coding stage, the concept formation stage, the categorization stage, and the theory formation stage. The findings show that external influences greatly affect the low data collection of non-permanent residents in the city of Payakumbuh